1989
DOI: 10.1136/ard.48.6.447
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus. I. Outcome and survival: Dutch experience with 110 patients studied prospectively.

Abstract: SUMMARY This report presents an analysis of the cumulative survival in 110 well defined patients with systemic lupus erythematosus (SLE) who were followed up over a prolonged period of time. Special attention was paid to possible differences between patients who died and those who were still alive at the end of the study. Of the 110 patients with SLE, 96 (87%) were still alive after 10 years; the cumulative survival for men was 69% (11/16) and for women 90% (85/94). Patients who never developed a new exacerbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0
3

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(55 citation statements)
references
References 23 publications
4
48
0
3
Order By: Relevance
“…9 10 In contrast, other authors identified thrombocytopenia as an important prognostic feature. [11][12][13] Ward et al added thrombocytopenia to nephritis and seizures as features which adversely affect survival. 1 Recently, Sultan et al associated thrombocytopenic manifestations with active disease in other organs, though none of these patients succumbed as a direct result of this complication.…”
Section: Discussionmentioning
confidence: 99%
“…9 10 In contrast, other authors identified thrombocytopenia as an important prognostic feature. [11][12][13] Ward et al added thrombocytopenia to nephritis and seizures as features which adversely affect survival. 1 Recently, Sultan et al associated thrombocytopenic manifestations with active disease in other organs, though none of these patients succumbed as a direct result of this complication.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that this improvement in survival has been accompanied by a shift in the predominant causes of death, with fewer deaths due to SLE and a greater proportion of deaths due to infections and the complications of atherosclerosis (3,7,(15)(16)(17)(18)20,24). Other investigators, however, report that SLE remains the most common cause of death (4,5,10-I 2, 14,19,[25][26][27][28][29]. Still others maintain that the predominant cause of death varies with the duration of disease, with SLE itself being the most common cause of death during the early years, and causes other than SLE responsible for most deaths later in the illness (3, 25,30).…”
mentioning
confidence: 99%
“…In addition to the 'classical' studies from Europe, [1][2][3] Canada, 4 or the United States (US) of America, 5 we now have reports from 'remote' areas such as Malaysia, 6 Kuwait, 7 Jamaica, 8 as well as many Latin-American countries, 9 to name just a few.…”
Section: Editorialmentioning
confidence: 99%